(untitled) (Journal of Naval Architecture and Marine Engineering, 2014)
The unsteady two-dimensional magnetohydrodynamic heat and mass transfer free convection flow of an incompressible viscous electrically conducting polar fluid through a porous medium past a semi-infinite vertical porous moving plate in the presence of a transverse magnetic field with thermal diffusion and heat generation is considered. The plate moves with a constant velocity in the longitudinal direction and the free stream velocity follows an exponentially increasing or decreasing. A uniform magnetic field acts perpendicularly to the porous surface which absorbs the polar fluid with a suction velocity varying with time. The equations of conservation of mass, momentum, energy and concentration which govern the case study of heat and mass transfer flow have been obtained. The equations have been solved numerically by Galerkin finite element method. The effect of various flow parameters are presented graphically. Representative results for velocity profiles, temperature profiles and concentration profiles are obtained for several values of pertinent parameters which are of physical and engineering interest. DOI: http://dx.doi.org/10.3329/jname.v11i1.12844